The first khan of Moghulistan in medieval sources and works of researchers - Akhmetkul , Серғазы; Bekmaganbetov, Өмірбай; Battalov, Қайрат (Turkic Studies Journal, 2023)
The article is based on the analysis of the domestic and foreign researches and examines data on the first khan of Moghulistan. Historians for a long time considered Tughluk - Timur to be the first khan of Moghulistan, which was created in the eastern part of the Chagatai Ulus. However, the works of British scholars of the second half of the 19th century refute this conventional point of view. Whereas V. Bartold, K. Pishchulina, V. Yudin, O. Akimushkin, O. Karaev and others justify that Tughluk - Timur Khan was the first khan of Moghulistan based on the data of ‘Muizz al-Ansab’, ‘Zafar-name,’ ‘Shajarat al-atrak’ and other works, then British scholars W. Erskine, E. Oliver and N. Elias based on the materials of ‘Tarikh-i-Rashidi’ by Muhammad Haidar, ‘Shajarayi Turk’ by Abulgazi describes Esen Buqa as the founder of the state of Moghulistan. However, the relative accuracy of the data provided in ‘Tarikh-i-Rashidi’ and ‘Shajarayi Turk’ makes it possible to consider Khan Esen Buqa to be the first khan of Moghulistan. These arguments cast doubt on the statements of V. Bartold, O. Akimushkin and others about the anachronism of the data of Muhammad Haidar and Abulgazi Bahadur Khan regarding Esen Buqa.